Disciplinarity versus interdisciplinarity (Urdimento: Revista de Estudos em Artes Cênicas, 2018)
In my work there is no research of an interdisciplinary theater, because I think that all theatrical forms are potentially there, and the history of theater teaches it. The theater has always welcomed the new emerging languages, making them, with time, part of themselves. In my work there is also no research aimed at merging different disciplines to go to a "non-theater of shadows", a "beyond the theater of shadows", which cancels the specifics of the genre. Rather. In my work there is only the need, strongly felt by me, of a theater of shadows finally inscribed and rooted in the present in which I live. An urgent need to adapt the theater of shadows to Western theatrical culture, to translate those principles that are the foundation of this art of the scene, in the forms and with the possibilities that are typical of the historical and geographical today in which I live.